Entre palavras e traços : um estudo da representação do sagrado cristão na poesia e na ilustração de José Régio - Fuza, Patrícia Josiane Tavares da Cunha (2007)
Jose Regio is known as one of the great names of the Portuguese Modernism Literature. As the director of the Literary Magazine Presença, he defended the spontaneous action and the sincerity to conceive the artistic creation. Inside the Presencismo (a literary movement in Portugal), the authors of that group gave an emphasis to the vision as a literary reason and also as a way to observe and to make interior questionings. Then, we can see the attention demonstrated by the group to the graphical and plastic aspects, as we can note in Jose Regio's work, which we will study in this research. Because of his expressive plastic simile, he could allow that the images emanated freely from his poetical production. Apart from being a writer, he was also an illustrator and painter, being recognized by those characteristics. Considered as a completed artist, Regio was capable to express his idea about the human, the world and the faith, through two readings: the text and the image. These two readings were reinforced to develop the subject that emerges detached in his production: the dialogue between the Human and the God, where the interior questioning makes the human to reevaluate the bases of his religious formation and to search the understanding of the Absolute as well. Although the religiousness is presented in his work, it constantly shocks with the necessity of the body pleasures. Thus, we have a sort of game between the sacred and the profane, where the sacred, represented by the Christ, by the Bible characters Adam and Eve, by angels and saints, became weak in the presence of the seduction of the profane thing. Therefore, the aim of this search is to verify the possible correspondences between ten of the poems and five of the illustrations from his book Poemas de Deus e do Diabo (1925), considering the theme about the representation of the sacred Christian figure. This research is based on the Comparative Method of analyzing literature, postulated by authors as Sandra Nitrini, Tania Carvalhal, among others, and also on the analysis of the poems and illustrations chosen. This research is justified by the necessity of detaching the image as an element which is presented in the structure of the text (language) and in the pictorial art as well; also, it is an artistic way where innumerable representations can be formed inside the reader's mind. Then, this work objects to contribute with the literary criticism about the author and about the artistic interchanging presented in the Jose Regio poetical production.